Perceived Family Support among elderly residing in Gokarneshwor Municipality, Kathmandu - Saud, Mithu; Pandey, Shrijana; Lama, Ishwori; Shrestha, Shova (Nepal Medical College Journal, 2023)
Family support is an essential factor among the elderly to maintain health and wellbeing. Most of the elderly are living with the family and depend on them for care. However support from family has been decreasing with the increasing age. The objective of the study was to assess perceived family support among elderly residing in Gokarneshwor, Kathmandu. A descriptive cross-sectional research design was used for conducting this study among 216 elderly residing in Gokarneshwor Municipality of Kathmandu over a period of July 2022 to October 2022 through non-probability purposive sampling technique. Data collection was done by using face to face interview using valid standard tool for family support scale (FSS). Data was analyzed by using SPSS version 16. The results of this study showed that more than half (55.1%) respondents perceived low family support from their family members. Only 44.9% had high family support. Respondents who had chronic disease were financially dependent perceived low family support. There was significant association between perceived family support and age (p=0.015), educational level (p=0.013) and working elderly (0.001). The study concluded that family support perception from elderly was low and some elderly was perceived high support from their family members. However sleep related care, information and decision making support was perceived less than other variables. Family members should be encouraged to build positive family relationship with elderly and involve them in wise decision making.